A Biomimetic Biphasic Scaffold Consisting of Decellularized Cartilage and Decalcified Bone Matrixes for Osteochondral Defect Repair - Cao, Runfeng; Zhan, Anqi; Ci, Zheng; Wang, Cheng; She, Yunlang; Xu, Yong; Xiao, Kaiyan; Xia, Huitang; Shen, Li; Meng, Depeng; Chen, Chang (Frontiers in Cell and Developmental Biology, 2021)
It is challenging to develop a biphasic scaffold with biomimetic compositional, structural, and functional properties to achieve concomitant repair of both superficial cartilage and subchondral bone in osteochondral defects (OCDs). This study developed a biomimsubchondraletic biphasic scaffold for OCD repair via an iterative layered lyophilization technique that controlled the composition, substrate stiffness, and pore size in each phase of the scaffold. The biphasic scaffold consisted of a superficial decellularized cartilage matrix (DCM) and underlying decalcified bone matrix (DBM) with distinct but seamlessly integrated phases that mimicked the composition and structure of osteochondral tissue, in which the DCM phase had relative low stiffness and small pores (approximately 134 μm) and the DBM phase had relative higher stiffness and larger pores (approximately 336 μm). In vitro results indicated that the biphasic scaffold was biocompatible for bone morrow stem cells (BMSCs) adhesion and proliferation, and the superficial DCM phase promoted chondrogenic differentiation of BMSCs, as indicated by the up-regulation of cartilage-specific gene expression (ACAN, Collagen II, and SOX9) and sGAG secretion; whereas the DBM phase was inducive for osteogenic differentiation of BMSCs, as indicated by the up-regulation of bone-specific gene expression (Collagen I, OCN, and RUNX2) and ALP deposition. Furthermore, compared with the untreated control group, the biphasic scaffold significantly enhanced concomitant repair of superficial cartilage and underlying subchondral bone in a rabbit OCD model, as evidenced by the ICRS macroscopic and O’Driscoll histological assessments. Our results demonstrate that the biomimetic biphasic scaffold has a good osteochondral repair effect.